Recent Advances in Arthroscopic Surgery - Wimal Amarasekera, Hiran (IntechOpen, 2018)
This book is aimed at providing an overview of arthroscopic joint surgery involving major joints in the body. It discusses all aspects of arthroscopy including complex surgical procedures, feasibility of performing surgery as an OPD procedure, and complications associated with these surgeries. The chapters are organised in regional basis and presented in an easy-to-understand format. This book will benefit all sports medicine physicians, orthopaedic surgeons and trainees, physiotherapists, and all clinicians involved in treating joint diseases. The combination of the authors' shared experiences with facts and presentation of figures and photographs will help the reader in understanding the complex principles involved. This can be used as a text for an individual or a "must have" reference book for any medical library.